Project 77 - Deschambault, Martin; Sparth (Quebec, Canada : ArtStation Media, 2017)
The dystopian sci-fi universe of Project 77 is finally unveiled. Having developed the ideas since childhood, Martin Deschambault, one of the principal artists from Ubisoft's Assasin's Creed, has created a mind-blowing world brought to life by a collection of captivating short stories by Jeffrey Campbell. Discover all there is to know on the history and process of the project and explore the intricacy of his technique and design. Deschambault takes you step by step in his in-depth tutorials, guiding you through the details of process for several of his illustrations in the book.
Keywords: Science fiction -- Illustrations; Dystopias in art -- Illustrations; Fantasy in art -- Illustrations; Computer art; Computer drawing; Science fiction in art; fantasy art -- Illustrations